Covalent Organic Framework Membranes for Efficient Chemicals Separation. Issue 10 (6th August 2021) - Wang, Rui; Guo, Jiaxing; Xue, Jian; Wang, Haihui
Abstract : Covalent organic frameworks (COFs) are an emerging class of organic porous crystalline materials that are composed entirely by organic linkers and connected by strong covalent bonds. The unique characteristics including well‐ordered and tailorable pore channels, high and permanent porosity, excellent thermostability and chemical stability, and ease of functionalization enable COFs to perfectly meet the requirements for the fabrication of advanced separation membranes. Significant progress has been made in the preparation and application of COF membranes over the past few years. Herein, the structure—performance relationship of COF materials on membrane separation is first proposed. The effects of the intrinsic properties of COF materials on membrane separation performance are systematically summarized. The fabrication methods of COF membranes, including both bottom‐up strategy (in situ growth and interface‐assisted synthesis) and top‐down strategy (blending and layer‐by‐layer [LBL] stacking), are then discussed in detail. The application of COF membranes in gas separation (H2 purification, CO2 capture, hydrocarbon separation) and liquid phase separation (water treatment, organic solvent nanofiltration, pervaporation) is highlighted. Finally, the remaining challenges and issues to be resolved in the COF membranes are prospected from the perspective of COF materials. Abstract : This review introduces the covalent organic frameworks (COFs) membranes in three parts. The first part discusses the structure—performance relationship of COF materials in membrane‐based separation. In the second part, the frequently used methods for the preparation of COF membranes are summarized. Finally, the representative reports on the applications of COF membranes for gas and liquid phase separation are described.